Gladiolus production as a function of growing environment conditions: a scientometric analysis - Santos, Bruno Henrique Vale dos; Caetano, Jordana Moura (Comunicata Scientiae, 2023)
Lately, an increase in the commercialization of gladiolus has been observed, making it necessary to know information that contributes to the optimization of its production. Such information can be obtained from the scientometric analysis. Thus, the objective of this work was to perform a scientometric analysis of the global scientific literature to quantify the studies on gladiolus and to specify in the Brazilian scientific literature the results of works on the cultivation environment. The scientometric analysis was performed in the Scopus database for the entire historical data series until the year 2021. A total of 1402 scientific papers published on gladiolus culture were obtained with an average publication rate equal to 0.62 papers year-1. These papers were mostly published as scientific articles in English language in journals focusing on horticulture and India is the country with the highest number of publications. About the cultivation environment, the studies conducted in Brazil indicate that the production of gladiolus should be carried out in periods that do not occur frosts and also for average air temperature below 35°C and soil humidity above 75% of field capacity. Despite the important results of these works, the global scientific literature still lacks more information that adequately assists in the increase of gladiolus production.